Makna dan Fungsi Ungkapan Pamali dalam Kehidupan Sosial Budaya Masyarakat di Desa Bendung Kabupaten Mojokerto: Kajian Etnolinguistik - Rafika Dini; Nada Vanca Anggrestia; Taswirul Afkar (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to explain the meaning and function of pamali, a form of taboo that is still applied as an unwritten rule of life in the people of Bendung Village, Jetis District, Mojokerto Regency. The method used in this research is descriptive qualitative. Data or information collection techniques in this research were obtained through literature study and interviews. The data that has been found will be analyzed using field data analysis techniques with an ethnolinguistic approach. The results of the research show that there are pamali that are still trusted by the majority of the people of Bendung Village, Jetis District, Mojokerto Regency. Some of these pamali include pamali for children, pamali for babies, pamali for pregnant women, pamali for women, and pamali for the general public. Pamali plays an important role in maintaining the norms and customs that apply in society. Pamali is considered a reflection of the unique and distinctive cultural values ​​of a community. The existence of pamali functions as a social regulatory tool that regulates individual behavior so that it conforms to norms recognized by society. Pamali has proven effective in creating safe and peaceful values ​​and norms in social life.